Pendampingan Praktik Penyelenggaraan Jenazah Melalui Metode Explicit Intruction di SMA Ma’arif NU Pandaan - Achmad Yusuf (LPPM Universitas Yudharta Pasuruan, 2020)
Abstract: This mentoring aims to provide knowledge and learning and experience directly to all students in organizing body management at SMA Maarif NU Pandaan. This accompaniment uses PAR debit via explicit instruction method. The results of this mentoring can increase the understanding of learners both from the theory and practical side, skills in organizing the body through explicit intruction. Improved process is known through the activities of students in the training and implementation of assistance by activities, while the increase of results can be known through student learning Achievement in the practice of the bodies of both individuals and groups.